Diagnosis and Etiologies of Monkey Pox Disease - Abdulkadir, Shina (Scientific Journal of Dermatology and Venereology, 2023)
Monkeypox in humans is transmitted through direct contact with infected animals or through the bite of an infected flea. This literature review aimed to describe the clinical aspects and management of monkey pox. Risk factors that can influence the spread of the monkey pox virus to humans are contact with infected animals, flea bites, travel history or being in monkeypox endemic areas, people with immunodeficiencies, age, and occupation factors. The clinical symptoms of monkeypox in humans are often similar to those of smallpox in humans. The time between infection and the onset of clinical symptoms usually ranges from 5 to 21 days, with an average of 12 days. Treatment of monkeypox is mostly supportive and aims to reduce symptoms and prevent complications. In order to prevent the spread of monkeypox, it is very important to avoid contact with animals infected with the monkeypox virus and to take other precautions, such as ensuring good hygiene and avoiding tick bites.